TINJAUAN YURIDIS TERHADAP PENGENAAN PAJAK BADAN DALAM USAHA PEER-TO-PEER LENDING BERBASIS FINANCIAL TECHNOLOGY (FINTECH): TINJAUAN YURIDIS PENGENAAN PAJAK USAHA PEER-TO-PEER LENDING BERBASIS FINTECH - Ngurah Bagus Pembayun Kepakisan; Adeline Melanie (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2022)
Fintech is the result of a combination of financial services and technology that changes the business model from conventional to moderate. One of the systems introduced through Fintech is Peer to Peer (P2P) Lending, which is a method of providing credit to individuals or businesses and vice versa, by applying for credit to P2P Lending business, which connects the borrowers with investors online. The problem that arises is that OJK has issued lists of P2P Lending who do not have permits, and most of these P2P Lending are legally qualified as business entities but not yet registered with OJK. Things that are reviewed are tax differences between P2P Lending with Unsecured Loan in banking, and tax resistance to P2P Lending business that are not registered with the OJK and do not carry out their tax obligations, along with tax sanctions against P2P Lending business that fight taxes. In conclusion, the imposition of taxes on P2P Lending is carried out in accordance with the Regulation of the Minister of Finance No. 69 of 2022 and if the P2P Lending are known and proven to have resisted taxes, they can be subject to sanctions in the form of administrative sanctions or criminal sanctions.